ANXIETY REDUCTION IN CHRONIC KIDNEY DISEASE (CKD) PATIENTS UNDERGOING HEMODIALYSIS THROUGH ACUPRESSURE AND QURANIC RECITATION INTERVENTIONS - Ariska, Maya; Supriyadi, Supriyadi; Endang Windiarti, Sri (Quality : Jurnal Kesehatan, 2025)
Background: Chronic Kidney Disease (CKD) is a progressive condition that leads to a gradual decline in kidney function, often requiring lifelong hemodialysis. Hemodialysis can negatively impact psychological well-being, particularly increasing anxiety, which affects the patient's quality of life. Non-pharmacological interventions such as acupressure and Quranic recitation have been utilized to reduce anxiety, but their combined effectiveness remains underexplored. Objective: This study aims to analysis the effect of acupressure therapy and Quranic recitationon anxiety levels in CKD patients undergoing hemodialysis, comparing their impact with a single intervention and a control group. Methods: A pretest-posttest experimental design with a control group was used. A total of 40 CKD patients undergoing hemodialysis were selected through simple random sampling. The intervention was administered twice a week for six weeks, consisting of acupressure at Ki-1, Li-4, and EX-3 points and Quranic recitation (Qira'ah Muzammil Hasballah) for 15 minutes. The control group received standard hospital procedures, including education and pharmacological therapy. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS) and analyzed with bivariate and multivariate tests. Results: The combination of acupressure and Quranic recitation significantly reduced anxiety (p=0.000<0.05). The combined therapy resulted in a 6.2-point reduction in anxiety, with an effect size of 0.05, making it the most effective intervention. Conclusion: Acupressure combined with Quranic recitationis effective in reducing anxiety in CKD patients undergoing hemodialysis and can serve as a complementary nursing intervention.